Guidlines for Choosing a System - Parthasarathy, S. (Journal of Information and Knowledge, 1986)
The use of microcomputers by libraries for housekeeping operations and information retrieval is now possible and economical. The hardware is now manufactured in India and available at affordable prices. But the application software packages are not readily available. Before automation is introduced, a proper evaluation of library's requirements, the software features needed and the hardware capabilities for implementing the software, has to be made. A suitable set of guidelines and criteria will be helpful for choosing a system.